2016
DOI: 10.1016/j.toxicon.2016.05.009
|View full text |Cite|
|
Sign up to set email alerts
|

Development and validation of a high-throughput online solid phase extraction – Liquid chromatography – Tandem mass spectrometry method for the detection of tetrodotoxin in human urine

Abstract: Tetrodotoxin (TTX) is an extremely potent paralytic toxin responsible for yearly illness and death around the world. A clinical measurement is necessary to confirm exposure because symptoms of TTX intoxication cannot be distinguished from other paralytic toxins. Our group has developed an online solid phase extraction hydrophilic interaction liquid chromatography (HILIC) method for the analysis of TTX in human urine with tandem mass spectrometry. The reportable range for the method was 2.80 - 249 ng/mL in urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Figure S1 shows the total ion chromatogram (TIC) and the selective product ions chromatograms of TTX with a concentration of 25 ng/mL. The results indicated that the appropriate product ions of TTX were 320.2 > 302.2 m / z ((corresponding to a loss of water, C 11 H 15 N 3 O 7 ), 320.2 > 162.2 m / z (C 9 H 8 N 3 O), and 320.2 > 284.2 m / z (C 11 H 14 N 3 O 6 ), which were consistent with those reported in the previous studies [ 41 , 42 ]. Moreover, among the three identified product ions, 320.2 > 302.2 m / z displayed the considerable superiority, which was considered as the quantitative ion during the determination of TTX for its high intensity.…”
Section: Resultssupporting
confidence: 91%
“…Figure S1 shows the total ion chromatogram (TIC) and the selective product ions chromatograms of TTX with a concentration of 25 ng/mL. The results indicated that the appropriate product ions of TTX were 320.2 > 302.2 m / z ((corresponding to a loss of water, C 11 H 15 N 3 O 7 ), 320.2 > 162.2 m / z (C 9 H 8 N 3 O), and 320.2 > 284.2 m / z (C 11 H 14 N 3 O 6 ), which were consistent with those reported in the previous studies [ 41 , 42 ]. Moreover, among the three identified product ions, 320.2 > 302.2 m / z displayed the considerable superiority, which was considered as the quantitative ion during the determination of TTX for its high intensity.…”
Section: Resultssupporting
confidence: 91%
“…Urinary excretion of TTX has been documented in humans and rats [ 23 , 27 ]. The results presented here indicate that repeated exposure of mice to TTX at doses of 75 and 125 µg/kg severely decreased urine production, which could be indicative of kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, pretreatment methods for TTXs can be divided into two parts: an extraction method and a purification method. Nevertheless, some techniques can extract target analytes and remove interfering substances simultaneously . Also, some approaches integrate extraction, purification, and preconcentration into a step. , Hence, we categorize existing pretreatment methods into several groups according to their technical characteristics and advances, which mainly include solid–liquid extraction, liquid–liquid extraction-based methods, and solid-phase extraction-based methods.…”
Section: Sample Preparationmentioning
confidence: 99%